Fibers, Geopolymers, Nano and Alkali-Activated Materials for Deep Soil Mix Binders - John Kok Hee Wong; Sien Ti Kok; Soon Yee Wong (Civil Engineering Journal, 2020)
Ordinary Portland Cement (OPC) and Lime (CaO) have traditionally been used as binder materials for Deep Soil Mix (DSM) ground improvement. Research has been conducted into possible alternatives such as pozzolans to reduce reliance on either cement or lime. However, pozzolans still undergo similar calcium-based reactions in the strengthening process. In this review, further alternative binder materials for soil strength development are explored. These recent developments include fiber reinforcement materials, alkali activation methods, nanomaterials and geopolymers, which can potentially achieve equal or improved performance. Research to date has shown that alkali-activated materials and geopolymers can be equivalent or superior alternatives to pozzolanic supplemented cement binders. The case is made for GP cements which potentially produces 80% less CO2 than conventional portland cement during manufacture. One-part AAM and GP cements are a promising substitute for portland cement in DSM. A combined approach which incorporates both Ca and alkali activated/geopolymer types of materials and hence reactions is proposed.